Optimalisasi Prestasi Belajar Pendidikan Kewarganegaraan Melalui Pendekatan Pemahaman Konsep di SMP - Kristanto, Agus (Universitas Muhammadiyah Surakarta, 2015)
This research aim to description about improvement of domination of matter comprehends democracy and goverment system in Indonesia through understanding of concept at class student VIII F in State Junior High School Three Teras Region Boyolali even semester of school year 2013/2014. Subject and research data source is 24 students. Data collecting method applies observation, questionnaire, documentation, and test. Data analysis applies critical analysis and comparability. Indicator success of using minimal limit criteria 75 and complete target of 100%. Research procedure applies cycle. Result of inferential research and solution as follows : obtained progress of achievement of student learning in study of Education Citizenship with matter comprehends democracy and goverment system in Indonesia , at precycle average of 71,6 and cycle I average of 76,2 and cycle II average of 84,8. From this data, seems to explain that happened increase of average of value from precycle to cycle I 4,6 numbers (6,4%), from cycle I to cycle II happened increase 8,6 numbers (11,3%), from pasiklus to cycle II happened increase 13,2 numbers (18,4%). Highest value of phase precycle 80 and cycle I 86 and cycle II 92. Seems to explain that from phase precycle to cycle I happened increase equal to 6 number (7,5%), from cycle I to cycle II happened increase equal to 6 number (7%), and from precycle to cycle II happened increase 12 numbers (15%). Low value of phase precycle is obtained by 66 and cycle I 72 and cycle II 76. thereby, can be affirmed that from phase precycle to cycle I happened increase equal to 6 number (6,1%), from cycle I to cycle II happened increase equal to 4 number (5,6%), and from precycle to cycle II happened increase 10 numbers (15,2%). Complete percentage learnt starts from precycle is obtained equal to 21% and cycle I is obtained equal to 50% and cycle II equal to 100%. Seems to explain that from phase precycle to cycle I happened increase equal to 29%, from cycle I to cycle II happened increase equal to 50%, and from precycle to cycle II happened increase equal to 79%.